2004
DOI: 10.2134/agronj2004.0700
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Corn and Soybean Yield to Soil and Terrain Properties

Abstract: yield data collected over many years in the same field and a larger set of measured soil and terrain variables Farmers will be better able to implement site-specific management would have a better chance of accomplishing this goal. practices when they understand the causes of spatial and temporal variability of corn (Zea mays L.) and soybean [Glycine max (L.) Data collection and analysis, however, are costly and Merr.] yield in their fields. Our objectives were to determine if a data labor-intensive, and quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 32 publications
9
89
2
5
Order By: Relevance
“…Dry years showed no differences at various topographic positions. Many studies have shown yearly differences in crop yields due to topography [18,19,[43][44][45][46]. In agreement with our results, Muñoz et al [44] also reported that topography had major influence on corn yields during the year with higher precipitation.…”
Section: Influence Of Topographic Position On Corn and Soybean Yieldssupporting
confidence: 91%
See 1 more Smart Citation
“…Dry years showed no differences at various topographic positions. Many studies have shown yearly differences in crop yields due to topography [18,19,[43][44][45][46]. In agreement with our results, Muñoz et al [44] also reported that topography had major influence on corn yields during the year with higher precipitation.…”
Section: Influence Of Topographic Position On Corn and Soybean Yieldssupporting
confidence: 91%
“…Thelemann et al [48] observed that higher water retention for longer periods of time resulted in lower corn grain and stover yields at depositional and flat areas, whereas well drained summit positions had the highest yields as these slope positions drained earlier. Depression areas can accumulate water in turn they can impact corn and soybean yields and significant difference in yield can be observed during wet and dry years of precipitation in these areas [46]. Depth to B horizon can play an important role in regulating yields at different topographic positions.…”
Section: Influence Of Topographic Position On Corn and Soybean Yieldsmentioning
confidence: 99%
“…In the northern area there was a certain tendency of higher yields, as observed for hyacinth bean 2002, (2002) and Kaspar et al (2004) point out that the higher the number of harvests monitored in the same area, the more precise and easier is the definition of differentiated land management zones. This corroborates the results reported here, since five of the seven harvests analyzed indicated the northern area as high-yield management zone.…”
Section: Crop Yieldmentioning
confidence: 86%
“…Elev. tend to have higher yield levels in years with above-average rainfall (Kaspar et al, 2004). Including corn grain yield from the previous growing seasons as a covariate in the autologistic models provided no improvements in predicting economic YR in all fi elds (data not shown).…”
Section: Spatial Variability In Economic Yield Responsementioning
confidence: 94%